2014
DOI: 10.1128/aem.00306-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of opsA , a Gene Involved in Solute Stress Mitigation and Survival in Soil, in the Polycyclic Aromatic Hydrocarbon-Degrading Bacterium Novosphingobium sp. Strain LH128

Abstract: The aim of this study was to identify genes involved in solute and matric stress mitigation in the polycyclic aromatic hydrocarbon (PAH)-degrading Novosphingobium sp. strain LH128. The genes were identified using plasposon mutagenesis and by selection of mutants that showed impaired growth in a medium containing 450 mM NaCl as a solute stress or 10% (wt/vol) polyethylene glycol (PEG) 6000 as a matric stress. Eleven and 14 mutants showed growth impairment when exposed to solute and matric stresses, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…In order to improve our general understanding of the process, recent studies have attempted to more systematically measure and interpret global reactions of introduced bacteria for bioremediation into complex systems (Fida et al ., 2012; 2013; Iino et al ., ; Maphosa et al ., ; Gunasekera et al ., ; Moreno‐Forero and van der Meer, ; Scheublin et al ., ). This has been complemented with global transposon mutagenesis approaches in order to identify gene functions with fitness benefit for growth and survival in soil (Roggo et al ., ; Fida et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In order to improve our general understanding of the process, recent studies have attempted to more systematically measure and interpret global reactions of introduced bacteria for bioremediation into complex systems (Fida et al ., 2012; 2013; Iino et al ., ; Maphosa et al ., ; Gunasekera et al ., ; Moreno‐Forero and van der Meer, ; Scheublin et al ., ). This has been complemented with global transposon mutagenesis approaches in order to identify gene functions with fitness benefit for growth and survival in soil (Roggo et al ., ; Fida et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…20−26 Studies showed that inoculation of soils with pollutant-degrading Sphingomonads was followed by a rapid decrease of number of CFU in the soil, directly after inoculation. 2,27 As for other organic pollutant degrading strains that show immediate decrease in CFU after soil inoculation, this decrease in CFU number is not wellunderstood.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Upon inoculation, strain LH128 shows a rapid decline in CFU numbers which increased afterward with concomitant removal of phenanthrene. 27 As a common practice in bioaugmentation procedures, the strain was cultured on a carbon source, i.e., glucose, that allows reaching relatively rapid high cell densities, and hence inoculation at high cell densities. The reason behind this decline in CFU numbers was explored by using a GFPexpressing variant of strain LH128 (LH128-GFP) enabling cultivation-independent counting of LH128 in aqueous soil extracts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In bioaugmentation strategies for contaminant bioremediation, the selected introduced bacteria have to establish interactions with a dynamic environment, and the balance between the cooperative and antagonistic forces will determine the outcome of this strategy ( 46 ). When bioaugmentation is required in rhizoremediation strategies, the biodegrading bacteria have to be metabolically active and have to be able to mineralize the contaminant.…”
Section: Discussionmentioning
confidence: 99%